2004
DOI: 10.1038/sj.gt.3302156
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno-associated virus-mediated alpha-1 antitrypsin gene therapy prevents type I diabetes in NOD mice

Abstract: Type I diabetes results from an autoimmune destruction of the insulin-producing pancreatic b cells. Although the exact immunologic processes underlying this disease are unclear, increasing evidence suggests that immunosuppressive, immunoregulatory and anti-inflammatory agents can interrupt the progression of the disease. Alpha 1 antitrypsin (AAT) is a multifunctional serine proteinase inhibitor (serpin) that also displays a wide range of anti-inflammatory properties. To test the ability of AAT to modulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 35 publications
5
88
0
Order By: Relevance
“…However, NOD mice are an exception and provide an excellent opportunity for studies of the immune response. In addition to high susceptibility for autoimmune disease such as type 1 diabetes and Sorgen's syndrome, NOD mice also display elevated immune responsiveness against foreign antigens and transgene products (16,21,22). The lack of immune response to transgene products from rAAV8 in the NOD mouse model strongly suggests that rAAV8 vector could be used in human clinical studies where immune response to transgene product must be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NOD mice are an exception and provide an excellent opportunity for studies of the immune response. In addition to high susceptibility for autoimmune disease such as type 1 diabetes and Sorgen's syndrome, NOD mice also display elevated immune responsiveness against foreign antigens and transgene products (16,21,22). The lack of immune response to transgene products from rAAV8 in the NOD mouse model strongly suggests that rAAV8 vector could be used in human clinical studies where immune response to transgene product must be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…However, the host immune response to a transgene product is one of the major hurdles to limit the successes of gene therapy in humans (19). Mingozzi et al have shown that restricted the transgene expression in liver using a liver-specific promoter in rAAV2 vector induced immune tolerance to the transgene product (F.IX) (20,21). Vandenberghe et al showed that AAV8 failed to activate a T-cell response to the AAV8 capsid because the capsid lacks a heparin binding domain (RXXR), which is important for DC transduc- tion (8).…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown to work in rodent models. [2][3][4][5][6][7] This area has been reviewed recently (see Bottino et al 8 ). Briefly, these strategies are aimed at inducing tolerance or hyporesponsiveness to islet autoantigens by either increasing tolerance inducing regulatory T lymphocytes (IL-10 gene therapy 2 ), suppressing reactive T lymphocytes (immunogene therapy using recombinant vaccinia virus expressing glutamic acid decarboxylase 3 or targeting these cells for apoptosis 6 ) or inducing tolerance in target cells (by overexpression of 'suppressor of cytokine signaling-1' 4 or by inducing antigen-presenting cells to express proinsulin, an autoantigen 5 ).…”
Section: Prospectsmentioning
confidence: 99%
“…Furthermore, abnormal variants of A1AT may themselves have pathogenic effects in the lung, as oxidatively modified or polymerized A1AT activate monocytes or attract neutrophils, respectively (14,15). Another noncanonical function of A1AT is that of apoptosis inhibition, exerted in lung microvascular endothelial cells (16,17) or pancreatic B cells (18). The work of Churg and colleagues expanded the knowledge of the mechanisms by which A1AT may exert other activities beyond neutrophil elastase inhibition (49).…”
Section: A1at Deficiency and Lung Diseasementioning
confidence: 99%
“…Bridging molecules, SP-A and -D are also decreased in the lungs of smokers (16), also potentially contributing to the defect. Of note, statins (17) and macrolides (18) were recently reported to enhance phagocytosis. This might help explain their anti-inflammatory properties and provide a mechanism of action to be pursued as therapy for COPD.…”
mentioning
confidence: 99%